Land suitability assessment for Banana and Pine Apple: A decision making approach using geo-spatial technology - GAHLOD, N. S.; BINJOLA, SONAM; KUMAR, MUNISH; ARYA, V. S. (Journal of Soil and Water Conservation, 2020)
The study was conducted to assess soil and land suitability for banana and pineapple in Kottayam district of Kerala. An inventory for soil resources on 1:50K scale was carried out using LISS-III satellite data. The generated database on soil and land resources under different soil series was rectified, georeferenced and assessed, comparing with the requirements of banana and pine apple crops in the GIS environment to classify area of district under different suitability classes. It was found that about 48.88 per cent of the area is suitable for banana cultivation in the district, out of which 2.35 percent, 8.63 percent and 37.90 percent were classified under highly suitable (S1), moderately suitable (S2) and marginally suitable (S3) classes, respectively. The results also indicated that about 8.30 percent and 34.58 percent of the study area was found under moderately suitable (S2) and marginally suitable (S3), respectively for pineapple crop. The area falling under not suitable (N) class for the cultivation of banana and pine apple was 34.16 and 40.16 percent, respectively. Topography, relief and water logging were found the main constraints for the cultivation of both crops. About 11.82 percent of area was classified under notified/restricted forest, whereas, 5.14 percent area under miscellaneous land uses like water bodies/river, habitation and rock out crop etc.